2011
DOI: 10.1136/injuryprev-2011-040146
|View full text |Cite
|
Sign up to set email alerts
|

Application of a public health framework to examine the characteristics of coroners' recommendations for injury prevention

Abstract: This study shows that highly evolved medicolegal death investigation systems may not draw systematically from the scientific research evidence base to inform the formulation of coroners' public health and safety recommendations. To maximise its contribution to fatal injury prevention, the medicolegal death investigation may benefit from incorporation of a public health perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
2
20
0
Order By: Relevance
“…Consistent with an earlier study,16 most of the coroners’ recommendations described the ‘countermeasure’ element. The countermeasures most often mentioned were research and education strategies at the policy level.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Consistent with an earlier study,16 most of the coroners’ recommendations described the ‘countermeasure’ element. The countermeasures most often mentioned were research and education strategies at the policy level.…”
Section: Discussionsupporting
confidence: 84%
“…We found that recommendations were made in less than 2% of external cause deaths of nursing home residents in Australia. Studies examining coroners’ recommendations following deaths from injury fatalities (6%, n=456) (Australia)16 and fatal heavy vehicle crashes (6%, n=21) (Australia)17 are consistent with this finding.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Some commentators have questioned the appropriateness of arming coroners with recommendation powers [3-5]. Criticism has also been levelled at the practicality and evidentiary basis of some recommendations [6-9]. However, the most prevalent concern, voiced in a succession of public inquiries [10-12], is that coroners’ recommendations are ineffective because the organisations and industries to which they are directed ignore them.…”
Section: Introductionmentioning
confidence: 99%